Cadaver Study of the Extension of the Lobes of the Thyroid Gland (Journal of Dhaka Medical College, 2010)
Context: The present study was designed to see the extension i.e. the superior and the inferior limits of the right and the left lobes of the thyroid gland of Bangladeshi people and compare with the previous studies. Study design: Descriptive type of study. Place and period of the study: Department of Anatomy, Dhaka Medical College, Dhaka from January to December 2008. Materials: The present study was performed on 60 post mortem human thyroid gland (39 of male and 21 of female) of unclaimed dead bodies which were in the morgue under examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. Methods: The samples were collected from the dead bodies by ‘block dissection' and upper and lower limits of the lobes of the thyroid gland were observed in situ and recorded. Results: The superior limit of the right and left lobes of the thyroid glands reached above the midpoint of the lamina of the thyroid cartilage in 16.67% and 8.33% cases and was found at the level of that midpoint in 41.67% and 43.33% of cases respectively. 41.67% on the right and 48.33% on the left could not reach that midpoint of the thyroid cartilage. The inferior limit of the right and left lobes of the thyroid gland reached up to the 5th tracheal ring in 63.33% and 60% cases respectively and inferiorly up to the 6th tracheal ring in 36.67% and 40% cases respectively. Key words: Thyroid gland; extension of lobes; superior and inferior limit. DOI: 10.3329/jdmc.v19i1.6252 J Dhaka Med Coll. 2010; 19(1) : 47-50.